Reinforcement Learning in Autism Spectrum Disorder - Schuetze, Manuela; Rohr, Christiane S.; Dewey, Deborah; McCrimmon, Adam; Bray, Signe (Frontiers in Psychology, 2017)
Early behavioral interventions are recognized as integral to standard care in autism spectrum disorder (ASD), and often focus on reinforcing desired behaviors (e.g. eye contact) and reducing the presence of atypical behaviors (e.g. echoing others' phrases). However, efficacy of these programs is mixed. Reinforcement learning relies on neurocircuitry that has been reported to be atypical in ASD: prefrontal-sub-cortical circuits, amygdala, brainstem and cerebellum. Thus, early behavioral interventions rely on neurocircuitry that may function atypically in at least a subset of individuals with ASD. Recent work has investigated physiological, behavioral and neural responses to reinforcers to uncover differences in motivation and learning in ASD. We will synthesize this work to identify promising avenues for future research that ultimately can be used to enhance the efficacy of early intervention.